The Muse of Urban Delirium: The Arts and Social Change in Transformational Cities - Ruble, B.A. (Социология: теория, методы, маркетинг, 2018)
It is argued that cities are shaped by the con frontation of reality and values as mitigated by the arts. More specifically, residents at the height of deep, profound, and rapid social, political, and economic change struggle to define and redefine their own identities. They often do so by creating new artistic forms which, over time, become respectable as they themselves move into the mainstream. The article explores moments when the performing arts helped new social movers define who they are in six different cities on five continents inventing new forms of opera, theater, music, and dance. These cities shared a protean drive unleashed by their rising social classes which were struggling to define their own distinct identities within the very turmoil their own emergence had created.